Betty Boop. IV - Fleischer, Dave, 1894-1979; Questel, Mae, 1910-1998; Poe, Bonnie, 1912-1993; Fleischer Studios Inc.; Cinetel Films ([Los Angeles, CA] : [publisher not identified], 2014)
Four episodes from the famous cartoon Betty Boop. The first episode in the series is in color.
Poor Cinderella -- Not now -- We did it -- The Betty Boop Limited -- From the dubbed version: Cenicienta pobretona -- No son horas -- Fuimos nosotros -- Un viaje con mucho ritmo.
Title from the provider's web page.
Originally produced in the United States as motion pictures between 1932 and 1936.
Produced by Fleischer Studios.
Movie distributed by Cinetel for Digitalia Film Library.
Voice: Bonnie Poe, Mae Questel.
Animated by Seymour Kneitel, Roland Chandall, William Henning, Willard Bowsky, George Germanetti.
Keywords: Boop, Betty (Fictitious character) -- Drama; Animated films; Comedy films; Internet videos; Streaming video